Engineered Fabrics - Kumar Singh, Mukesh (IntechOpen, 2019)
Engineered fabrics have gained special attention from all quarters due to their adaptability for unconventional applications. Engineered fabrics are used in a range of technical products such as seatbelt fabrics, automotive textiles, geotextiles, and other industrial textiles. This book provides a comprehensive review and case studies of engineered fabrics used in civil engineering as geotextiles. Engineered fabrics cover a huge area from textiles used for deep-sea applications to reinforcing materials for lightweight composite materials used to construct various aircraft panels. This book gives an insight into soil conservation using engineered fabrics along with woven denim fabrics with dual core-spun yarns. The editor has included one introductory chapter on engineered fabrics that covers all aspects of fabric engineering required to cater for the needs of technical and industrial textiles.